Holly : a novel - King, Stephen, 1947- (New York : Scribner, 2023)
Formerly shy private detective Holly Gibney reluctantly agrees to search for a client's missing daughter, which may have something to do with an unholy secret being harbored in the basement of a pair of semi-retired octogenarian academics.
Maine author.
Keywords: Women private investigators -- Fiction; Private investigators -- Fiction; City and town life -- Fiction; Criminal investigation -- Fiction; Secrecy -- Fiction; Older couples -- Fiction; Missing children -- Fiction; Horror fiction; Psychological fiction; Thrillers (fiction).; Detective and mystery fiction